Chile & Rapa Nui 2025 - Johanson, Mark (Travel writer); Albiston, Isabel; Raub, Kevin; Freeman, Bailey; Yanagihara, Wendy (Lonely Planet guidebooks., 2025)
Lonely Planet's local travel experts reveal all you need to know to plan the trip of a lifetime in this latest edition of our guide to Chile & Rapa Nui (Easter Island). Discover Chile & Rapa Nui (Easter Island)'s most popular experiences and best kept secrets from surfing one of the most famous waves in the Americas, the perfect left break at Punta de Lobos; to catching a mind-melting sand dune sunset of surreal purples, pinks and yellows at Valle de la Luna; and visiting the most opulent wineries in Chile's Colchagua Valley.